Aberrant resting-state cerebellar blood flow in major depression - Depping, Malte S.; Wolf, Nadine D.; Schmitgen, Mike; Wolf, Robert Christian (Journal of affective disorders, 2018)
Background: Abnormal cortical cerebral blood ﬂow and gray matter volume have been frequently reported in patients with major depressive disorder (MDD). In contrast, although the role of the cerebellum in MDD pathophysiology has attracted considerable interest more recently, studies investigating both functional and structural aspects of cerebellar integrity are scarce. Methods: In this study, we used structural and functional magnetic resonance imaging (MRI) to investigate cerebellar volume and regional cerebellar blood ﬂow (rCBF) at rest in clinically acute MDD patients (n = 22) and healthy controls (n = 18). We acquired high-resolution structural images at 3 T together with perfusion images obtained with continuous arterial spin labeling. Cerebellar structure and function were investigated using cerebellum-optimized analysis techniques. Results: Markedly increased rCBF was found in bilateral cerebellar areas VIIa and VIIIb (p < 0.05 family-wiseerror [FWE] corrected). Signiﬁcant diﬀerences in cerebellar volume between patients and controls were not found (p < 0.05, FWE-corrected). Left cerebellar area VIIa perfusion was signiﬁcantly associated with depressive symptoms, as measured by the Hamilton Depression Rating Scale. Limitations: Potential limitations of this study include the modest sample size, the cross-sectional design, the lack of task-related imaging and the heterogeneity of drug treatment. Conclusions: The data suggest contributions of “aﬀective” cerebellar regions to MDD pathophysiology and symptom expression. While cerebellar perfusion at rest is compromised in MDD, cerebellar volume seems to be less aﬀected.
Available online 28 September 2017
Gesehen am 10.12.2018